Populism in Europe : Lessons from Umberto Bossi's Northern League - Albertazzi, Daniele, 1968-; Vampa, Davide (Book collections on Project MUSE., 2021)
Populism in Europe offers a detailed and systematic analysis of the ideology, electoral and governmental performances, organisational model, type of leadership and member activism of the Northern League under its founder, Umberto Bossi (1991-2012). Based on a wealth of original research, the book identifies the Northern League's consistent and coherent ideology, its strong leadership and its ability to create communities of loyal partisan activists as key ingredients of its success. Through their in-depth analysis, Albertazzi and Vampa show that the League has much to teach us about how populists can achieve durability and rootedness and how parties of all kinds can still benefit from a committed and dedicated membership today. --